Effects of nicotine on the biosynthesis of carotenoids in halophilic Archaea (class Halobacteria): an HPLC and Raman spectroscopy study - Oren, Aharon; Hirschberg, Joseph; Mann, Varda; Jehlička, Jan (Extremophiles, 2018)
Nicotine has a profound influence on the carotenoid metabolism in halophilic Archaea of the class Halobacteria. In a study of Halobacterium salinarum, Haloarcula marismortui and Halorubrum sodomense, using different analytical techniques to monitor the production of different carotenoids as a function of the presence of nicotine, we showed that the formation of α-bacterioruberin was inhibited in all. In Hbt. salinarum, addition of nicotine led to a significant change in the color of the culture due to the accumulation of lycopene, in addition to the formation of bisanhydrobacterioruberin which does not differ in color from α-bacterioruberin. Very little or no lycopene was formed in Har. marismortui and in Hrr. sodomense; instead bisanhydrobacterioruberin was the only major carotenoid found in nicotine-amended cultures. The findings are discussed in the framework of the recently elucidated biochemical pathway for the formation of the different carotenoid pigments encountered in the Halobacteria.
Keywords: Haloarchaea; nikotin; nikotinoví agonisté; Nicotinic Agonists; Bacterioruberin; Nicotine; Carotenoids; Euryarchaeota; karotenoidy